2001
DOI: 10.1002/etc.5620200206
|View full text |Cite
|
Sign up to set email alerts
|

Biological response to variation of acid‐volatile sulfides and metals in field‐exposed spiked sediments

Abstract: Vertical and temporal variations of acid-volatile sulfides (AVS) and simultaneously extracted metals (SEM) in sediment can control biological impacts of metals. To assess the significance of these variations in field sediments, sediments spiked with cadmium, copper, lead, nickel, and zinc were deployed in Narragansett Bay for four months and recolonization by benthic organisms investigated. In surface sediments, concentrations of AVS decreased with time whenever AVS exceeded SEM but remained unchanged when AVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…1), demonstrating the importance of AVS for Ni partitioning. Porewater Ni variability when (SEM À AVS) approached zero was similar to that reported in earlier studies [10,38,39]. This variability of pore-water Ni is consistent with the low affinity of Ni for the AVS in comparison with that of Cu, Pb, Cd, and Zn, which results in Ni appearing first in the pore water as concentrations of SEM increase relative to that of AVS [33,40].…”
Section: Study Site Characteristics and Sediment Geochemistrysupporting
confidence: 87%
See 1 more Smart Citation
“…1), demonstrating the importance of AVS for Ni partitioning. Porewater Ni variability when (SEM À AVS) approached zero was similar to that reported in earlier studies [10,38,39]. This variability of pore-water Ni is consistent with the low affinity of Ni for the AVS in comparison with that of Cu, Pb, Cd, and Zn, which results in Ni appearing first in the pore water as concentrations of SEM increase relative to that of AVS [33,40].…”
Section: Study Site Characteristics and Sediment Geochemistrysupporting
confidence: 87%
“…If (SEM À AVS) 0 (SEM/ AVS 1), the pore-water metal concentrations should be low, and no toxicity to sediment organisms should be observed [1,4,5]. The influence of AVS on sublethal metal toxicity to benthic organisms also has been evaluated, using long-term laboratory assays [6][7][8][9] and field studies [10][11][12][13]. Next to sulfide binding, other factors affect metal bioavailability, such as organic carbon, iron and manganese oxyhydroxides, and particle size [5,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This is more consistent with previous observations (e.g. Boothman et al 2001), and may be the result of coarser sediments, a more stable hydrological environment, or some combination of these and other factors.…”
Section: -49supporting
confidence: 93%
“…Other authors have found metal concentrations in marine sediments to increase with increasing sediment depth (e.g. Boothman et al 2001), and have hypothesized that shallower sediments lose metals as a result of bioturbation, physical turbulence, and diffusive processes. However, these observations were made on sediments spiked with metals, and at a coarser spatial resolution than what was measured in this study.…”
Section: Dgtsmentioning
confidence: 99%
“…Based on the Cu-DGT measurements, however, it was demonstrated that available concentrations of metals in interstitial waters were low and hence biological impacts were undetectable. Similarly, due to low bioavailability, recolonization by benthic organisms was not affected on field incubated metal spiked freshwater (Boothman et al, 2001) and marine sediments.…”
Section: Discussionmentioning
confidence: 94%